The role of OATP1B1 and OATP1B3 transporter polymorphisms in drug disposition and response to anticancer drugs: a review of the recent literature. (3rd August 2022) - Anabtawi, Nadeen; Drabison, Thomas; Hu, Shuiying; Sparreboom, Alex; Talebi, Zahra
ABSTRACT: Introduction: Members of the solute carrier family of organic anion transporting polypeptides are responsible for the cellular uptake of a broad range of endogenous compounds and xenobiotics in multiple tissues. In particular, the polymorphic transporters OATP1B1 and OATP1B3 are highly expressed in the liver and have been identified as critical regulators of hepatic elimination. As these transporters are also expressed in cancer cells, the function alteration of these proteins have important consequences for an individual's susceptibility to certain drug-induced side effects, drug–drug interactions, and treatment efficacy. Areas covered: In this mini-review, we provide an update of this rapidly emerging field, with specific emphasis on the direct contribution of genetic variants in OATP1B1 and OATP1B3 to the transport of anticancer drugs, the role of these carriers in regulation of their disposition and toxicity profiles, and recent advances in attempts to integrate information on transport function in patients to derive individualized treatment strategies. Expert opinion: Based on currently available data, it appears imperative that different aspects of disease, physiology, and drugs of relevance should be evaluated along with an individual's genetic signature, and that tools such as biomarker levels can be implemented to achieve the most reliable prediction of clinically relevant pharmacodynamic endpoints.